Alginate Hydrogel Beads with a Leakproof Gold Shell for Ultrasound-Triggered Release - Marcus Flowers; Alex Paulsen; Claire R. W. Kaiser; Adam B. Tuma; Hubert H. Lim; Brenda M. Ogle; Chun Wang (Pharmaceutics)
Background/Objectives: Focused ultrasound has advantages as an external stimulus for drug delivery as it is non-invasive, has high precision and can penetrate deep into tissues. Here, we report a gold-plated alginate (ALG) hydrogel system that retains highly water-soluble small-molecule fluorescein for sharp off/on release after ultrasound exposure. Methods: The ALG is crosslinked into beads with calcium chloride and layered with a polycation to adjust the surface charge for the adsorption of catalytic platinum nanoparticles (Pt NPs). The coated bead is subject to electroless plating, forming a gold shell. Ultrasound is applied to the gold-plated ALG beads and the release of fluorescein with or without ultrasound stimulation is quantified. Results: Polyethylenimine (PEI), not poly-L-lysine (PLL), is able to facilitate Pt NP adsorption. Gold shell thickness is proportional to the duration of electroless plating and can be controlled. Gold-plated ALG beads are impermeable to the fluorescein cargo and have nearly zero leakage. Exposure to focused ultrasound initiated the release of fluorescein with full release achieved after 72 h. Conclusions: The gold-plated ALG hydrogel is a new material platform that can retain highly water-soluble molecules with a sharp off/on release initiated by focused ultrasound.